A flexible pH sensor based on the iridium oxide sensing film - Huang, Wen-Ding; Cao, Hung; Deb, Sanchali; Chiao, Mu; Chiao, J.C. (Sensors and actuators. A. Physical., 2011)
We have developed a novel flexible pH sensor based on a polymeric substrate by low-cost sol–gel fabrication process of iridium oxide (IrO x ) sensing film. A pair of miniature IrO x /AgCl electrodes on a flexible substrate generated electrical potentials in solutions by electrochemical mechanisms responding to their pH levels. Our flexible IrO x pH sensors exhibited promising sensing performance with a near-Nernstian response in sensitivity repeatedly and reversibly between −51.1 mV/pH and −51.7 mV/pH in the pH range between 1.5 and 12 at 25 °C. The fabrication processes including sol–gel deposition, thermal oxidation, and AgCl electro-plating on polymeric substrates were reported. The performance and characterization of the flexible pH sensors in sensitivity, response time, stability, reversibility, repeatability and selectivity were also discussed. Our IrO x pH electrodes on a deformable substrate demonstrated their sensing capability while they were conformed to a curved surface inside a limited space with distinct responding potentials at various pH levels similar to the traditional glass-rod pH electrodes.